Perfection of an Energy-Economic and Environmental Parameters of the Ground Source Heat Pump Systems with Preventing Freezing of the Soil around Ground Pipes - Dnisova A.E.; Ivanov P.O.; Mazurenko A.S.; Zhaivoron O.S. (Problems of the Regional Energetics)
This article is devoted to the methods for perfection of energy, economic factors, environmental factors and work modes of the ground source heat pump systems with the account of climate conditions. The purpose of the work is to predict and prevent freezing of the soil during long term of exploitation of the low-power and high-power ground source heat pump systems for jus-tifying rational conditions of implementation GSHP in Ukraine and South-East Regions of Eu-rope. This goal is achieved by solving the following problems: determining the energy-economic and environmental factors based on considering the work modes of the ground source heat pumps; evaluation of the operating efficiency of ground source heat pump systems based on minimizing fuel consumption and greenhouse gas emissions; perfection of solutions enable im-plementation of ground source heat pumps friendly to the environment and justifying rational conditions of implementation the ground source heat pumps for residential sector. The important results of the work are the obtained and analyzed data on the influence of energy and economic factors both environmental criteria on the work modes and scheme-constructive solutions of ground source heat pumps. Modeling of heat exchange processes in the soil around the soil tube shows that in order to avoid freezing of the soil, the minimum permissible specific number of vertical tubes should be at least 0.12–0.15 pieces/m2 of heated area. The significance of the re-sults consists in the possibility of using the results of numerical simulation for preventing freez-ing of the soil around ground pipes of the ground source heat pump systems.